FARMERS LEVEL OF KNOWLEDGE ON THE USAGE OF PESTICIDES AND THEIR EFFECTS ON HEALTH AND ENVIRONMENT IN NORTHERN PAKISTAN - Abdullah A. AL-Zaidi; Mirza B. Baig; S. El-Tayeb Muneer; S. M. Hussain; F. O. Aldosari (Journal of Animal and Plant Sciences, 2019)
Inappropriate applicationof pesticides can cause health issues among the farmers, children, and field workers. High dependence on pesticides for pest control by illiterate and untrained farmers has increased health hazards and polluted the agricultural environment in Pakistan. The prime purpose of the study was to make an assessment of the level of knowledge of contact farmers on the proper usage of pesticides in district Peshawar, Pakistan.A simple random sample of 300 farmers for the study purposes was drawn out of the total population of 4200 farmers living in the study area. Data were collected using a pre-tested questionnaire translated into the local language. Personal face-to-face interviews of the contacted farmers from all the 4 towns of the district Peshawar, Pakistan were conducted to meet the objectives of the study. The study revealed that the most important factors responsible for the problems caused by the pesticide applications include: low education level of the rural population, lack of information and training on the safe application of pesticides, poor spraying technology, and inadequate personal protection during pesticide application. About two thirds of the respondents (61.7%) get information from agricultural extension service providers; nearly half of the respondents sometimes get information from TV and Radio; while more than half (55.7%) of the respondents reported that they received average level trainings on pesticides. The study revealed that about two thirds (63.3%) of the contact farmers had enough awareness on the safe usage of pesticides and their hazardous effects on health and environment. However, it was noticed that the knowledge alone is rarely translated into actions. Many other factors like farmers’ available resources and socioeconomic characteristics also play a significant role.There is a need to improve information exchange about pesticide-related issues between contact farmers and their sources of information, and to focus more on the sources from which the farmers get the least information, such as agricultural literature and programs on TV and radio. It is suggested to improve agriculture extension education programs and to include awareness campaigns about proper usage of pesticides for the capacity building of contact farmers. Alternate methods of pest control should be encouraged. Agricultural extension activities like farmer field schools on integrated pest management (IPM) deserve to be promoted.
Keywords: Bio-safety; Capacity building; Environment; Extension education; Health; Knowledge levels; Pesticides; Technology transfer